“A DETAILED DESCRIPTIONS OF DINCHARYA WITH SPECIAL REFERENCES OF BRIHATTRAYI” (International Journal of Food and Nutritional Sciences, 2022)
According to ancient research methodology, before establishing any theory, the findings should be subjected through some sequential steps. The research work is done to draw some conclusion (Nigamana) from the findings an results. To communicate the findings with the results, more fare study (Upanaya) is needed. It is the process to re-examine the whol work. Upanaya form a firm base for Nigamana. In spite of detailed classical study and experimentation, a theory can be accepted only aft proper reasoning of observations. Hence, the discussion is very much important part of any scientific research. It can either support the hypothesis or it can help in amendment or it may revolutionize the concept totally. The present study entitled the conceptual study on Dincharya with special references to the brihattrayi, also called as greater ancient literatures of Ayurveda viz Charak Samhita, Sushruta Samhita and Ashtanga Hridayam, has been specially undertaken to define and evolve objective parameter for the entity of Regimen which is a very important concept of Ayurveda. Although the production of many diseases depends upon this pathogenic factor, but still there is no objective parameter to identify the entity.